26th Annual Meeting of the International Society of Chemical Ecology - Keller, Tina (2010)
The Mozambique tilapia is a lek-breeding cichlid wherein males establish dominance hierarchies and visiting females mate preferentially with dominant territorial males. Dominant males increase urination frequency during courtship and aggression (1). A sulphated aminosterol urinary odorant for females has been suggested to act as pheromonal signal of dominance, thereby influencing female spawning (1). Here, we address whether both sexes detect the same odorants in the urine of males of different social rank by recording of the electro-olfactogram (EOG) in response to HPLC fractions of male urine. Urine volume collected from dominant males was larger than that collected from subordinate males and positively correlated with relative bladder tissue weight. The olfactory system of both sexes was more sensitive to dominant male urine and corresponding C18 solid phase extracts than to those of subordinates. HPLC of these extracts revealed a well retained peak on a Evaporative Light Scattering detector with significantly larger relative area in dominant than in subordinate males. The HPLC fractions containing this peak, assumed to be the amino-sterol odorant, evoked concentration-dependent EOG amplitudes in both sexes. In contrast, the EOG amplitudes elicited in both sexes by another HPLC fraction containing nonretained peaks were not significantly different among males of different social rank. The results suggest that an increase of the amino-sterol urinary odorant signals dominance to both sexes in a blend comprising another not yet identified urinary odorant(s). References cited 1. Barata, E.N. et al. 2008. Journal of Chemical Ecology 34:438–449. Acknowledgement to FCT (Portugal) for funding SFRH/BD/46192/2008.